2004
DOI: 10.1542/peds.113.1.e51
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral Infections in Children: The Impact of Rapid Diagnosis

Abstract: ABSTRACT. Background. Adenovirus (ADV) infections were difficult to diagnose in the past, and many infections were unrecognized. Direct fluorescent assay (DFA) for the rapid diagnosis of ADV infection, as part of a viral respiratory panel, became available at Primary Children's Medical Center (Salt Lake City, UT) in December 2000.Objective. To describe children with ADV infection diagnosed by DFA and viral culture and document the impact of rapid ADV testing on patient care.Methods. DFA testing for respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
92
1
11

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(116 citation statements)
references
References 31 publications
4
92
1
11
Order By: Relevance
“…HAdVs are ubiquitous in human populations, especially in infants (Pauly et al, 2014;Rocholl et al, 2004). To date, approximately 70 HAdV types have been identified and classified into seven species, Human mastadenovirus A to G (HAdV-A to HAdV-G).…”
Section: Introductionmentioning
confidence: 99%
“…HAdVs are ubiquitous in human populations, especially in infants (Pauly et al, 2014;Rocholl et al, 2004). To date, approximately 70 HAdV types have been identified and classified into seven species, Human mastadenovirus A to G (HAdV-A to HAdV-G).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Infections can cause localized disease such as enteritis, upper respiratory tract infection, encephalitis or cystitis. [13][14][15] However, AdV infections in immunocompromised patients tend to become invasive, and disseminated disease is associated with very high mortality. 3,11,16 We have established a pan-adenovirus real-time PCR assay and demonstrated that AdV detection in peripheral blood (PB) of patients during the post-transplant period is associated with very high morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to HCT, some patients were reported to have developed fulminant hepatic failure after liver transplantation (22)(23)(24)(25)(26)(27) or renal transplantation (28), or after chemotherapy without undergoing HCT (29)(30)(31)(32)(33). Moreover, other cases were reported without having had any immunosuppressive treatment (34), or some were immunocompetent cases (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic options for ADV disseminated disease are still very limited (1,7,10,36,38,39,41,43,(45)(46)(47). Intravenous or aerosolized ribavirin (1,7,19,38,45,47), vidarabine (7), and cidofovir (7,36,(45)(46)(47) are included in antiviral agents, and the intravenous administration of immunoglobulin (12), the discontinuation of antibiotics (36), donor lymphocyte infusion (7) (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation